Dual-energy CT-based nomogram for predicting progression-free survival in locally advanced nasopharyngeal carcinoma - Pei, Wei; Wang, Chen; Wei, Yunyun; Xie, Jisheng; Su, Danke; Liao, Hai (Frontiers in Oncology, 2025)
PurposeTo establish a dual-energy CT (DECT) based nomogram for predicting progression-free survival (PFS) in locally advanced nasopharyngeal carcinoma (LANPC).MethodsIn this retrospective study, 52 LANPC patients who underwent DECT scans and post-treatment follow-up (median follow-up = 42.2 months) were enrolled. DECT parameters of tumor lesions including iodine concentration (IC), normalized iodine concentration (NIC), the slope of the spectral Hounsfield unit (HU) curve (λHU), and effective atomic number (Zeff) were analyzed to predict PFS. A nomogram integrating clinical data and DECT-derived parameters was constructed. The model’s performance was evaluated using calibration curves, Harrell’s concordance index (C-index), and receiver operating characteristic (ROC) curve.ResultsNIC, neutrophil-to-lymphocyte ratio (NLR), and lactate dehydrogenase (LDH) were the independent prognostic factors for PFS, and were incorporated into constructing the nomogram. Calibration plots demonstrated strong agreement between predicted and observed PFS rates. The C-index for the nomogram was 0.88 (95% confidence interval [CI]: 0.80–0.90). The nomogram model demonstrated predictive accuracy for PFS, with the area under the ROC curves (AUCs) of 0.939, 0.880, and 0.879 at 1-, 2-, and 3-year, respectively.ConclusionThe DECT-based nomogram exhibited excellent predictive accuracy for PFS in LANPC patients, highlighting its potential as a valuable clinical tool.